FAG Salmonella ASAL LIMBAH PASAR IKAN DAN AIR SUNGAI DI SEKITAR KAMPUS UNIVERSITAS BANGKA BELITUNG - Rizky Putri Deshanda; Rahmad Lingga; Nur Annis Hidayati; Eka Sari; Rossy Hertati (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2018)
Seven Salmonella lytic phages found in water sample of river near UBB campus building. Phages were characterized by plaque morphology (plaque diameter size and shape) and phage host range. Phages formed plaques with diameter size ranges from 1.06 mm to 4.90 mm, and form shape such as small dot, circle, elongated, or irregular. Factors effect plaque forming by phages are phage titer number and incubation time. All phage isolates have broad host range include Gram negative and positive. Six phage isolates are able to lyse Salmonella, Staphylococcus aureus, and Escherichia coli, meanwhile one phage isolate is able to lyse Salmonella and Staphylococcus aureus.